Nurses´ perceptions of automated dispensing cabinets - an observational study and an online survey - Riikka Metsämuuronen; Hannu Kokki; Toivo Naaranlahti; Minna Kurttila; Reeta Heikkilä (BMC, 2020)
Abstract Background Thirty-two automated dispensing cabinets (ADCs) were introduced in May 2015 in Kuopio University Hospital, Finland. These medication distribution systems represent relatively new technology in Europe and are aimed at rationalising the medication process and improving patient safety. Nurses are the end-users of ADCs, and it is therefore important to survey their perceptions of ADCs. Our aim was to investigate nurses' perceptions of ADCs and the impacts of ADCs on nurses' work. Methods The study was conducted in the Anaesthesia and Surgical Unit (OR) and Intensive Care Unit (ICU), of a tertiary care hospital, in Finland. We used two different research methods: observation and a survey. The observational study consisted of two 5-day observation periods in both units, one before (2014) and the other after (2016) the introduction of ADCs. An online questionnaire was distributed to 346 nurses in April 2017. The data were analysed using descriptive statistics including frequencies and percentages and the Chi-Square test. Results The majority (n = 68) of the 81 respondents were satisfied with ADCs. Attitudes to ADCs were more positive in the ICU than in the OR. Nearly 80% of the nurses in the ICU and 42% in the OR found that ADCs make their work easier. The observational study revealed that in the OR, time spent on dispensing and preparing medications decreased on average by 32 min per 8-h shift and more time was spent on direct patient care activities. The need to collect medicines from outside the operating theatre during an operation was less after the introduction of ADCs than before that. Some resistance to change was observed in the OR in the form of non-compliance with some instructions; nurses took medicines from ADCs when someone else was logged in and the barcode was not always used. The results of the survey support these findings. Conclusions Overall, nurses were satisfied with ADCs and stated that they make their work easier. In the ICU, nurses were more satisfied with ADCs and complied with the instructions better than the nurses in the OR. One reason for that can be the more extensive pilot period in the ICU.